The beneficial role of companion animals in translational pain research - Lascelles, B. Duncan X.; Brown, Dottie C.; Conzemius, Michael G.; Gill, Marie; Oshinsky, Michael L.; Sharkey, Michelle (Frontiers in Pain Research, 2022)
The use of spontaneous painful disease in companion pet animals has been highlighted as one of the changes that could be made to help improve translation of basic science to new therapeutics, acting as a bridge between preclinical and clinical studies, with the goal of accelerating the approval of new therapeutics. This review focuses on the utility of companion pet dogs for translational research by reviewing what outcome measures can be measured, and importantly, the relevance of these outcome measures to human translational research. It also details the practical considerations involved in incorporating companion dogs into human therapeutic development.